Discovery Of New Targeting Agents Against Gapdh Receptor: In Silico And In Vitro Studies - Noh, Muhammad Amirul Asyraf (2023)
Tuberculosis (TB) is one of the leading causes of death due to a single infectious agent worldwide and one of the suggestions to overcome this disease is by using targeted drug delivery. Glyceraldehyde-3-Phosphate Dehydrogenase (GAPDH), a multifunctional protein and virulence factor in pathogenic microorganisms is suitable to be the designated drug target as it has been located on the cell surface of Mycobacterium tuberculosis (M. TB) recently. This research is focused on finding the suitable targeting molecules towards GAPDH that can be used for the development of targeted antituberculosis agents. Around 14 molecules with previously reported in vitro and/or in vivo activities against GAPDH or usages as targeting agents were assessed for their binding affinity through molecular docking technique using AutoDock 4.2. Among these 14 molecules, folic acid, NP-014428 and CGP 3466 were discovered to possess the best binding affinity with GAPDH. 13 derivatives of folic acid were then docked against GAPDH. F7 (folic acid N-hydroxysuccinimide ester) and F8 (γ-{[tert-butyl-N-(2-aminoethyl)]carbamate} folic acid) were discovered to possess the most favourable binding affinity among the folic acid derivatives. Consequently, F7 and folic acid were sent to undergo molecular dynamics (MD) simulations with GAPDH using GROMACS 2021.2 alongside NAD (nicotinamide adenine dinucleotide), the natural ligand of GAPDH as positive control agent. Compared to the NAD/GAPDH complex, folic acid/GAPDH complex has the most stable conformation but with the weakest binding affinity whereas F7/GAPDH complex having the most unstable conformation but has the strongest binding affinity.